Organising healthcare with multi-professional teams:: Activity coordination as a logistical flow - Gadolin, Christian; Wikström, Ewa (Scandinavian Journal of Public Administration, 2016)
Multi-professional teams are now common when organising healthcare. Such teams are considered to resolve fragmentation issues amongst units and their functions, facilitate efficient and high quality care and are also deemed to enable different professions to meet and exchange experience and knowledge. The expected consequence is superior decisions and improved care. However, research suggests that the deployment of multi-professional teams within healthcare organisations is problematic with regard to knowledge sharing and integration between different professional groups. While often recognised, the reason for this shortcoming has rarely been explored in depth. This study consequently elaborates on the factors hindering knowledge sharing through illustrating and discussing the logics of different professional groups and the ensuing consequences when multi-professional teams interact. The finding is that the teams are being utilised by the medical professions in accordance with their professional logic. This results in the coordination of activities, incorporating the patient flow logistics amongst the different professions; making the impact of multi-professional teams concrete in practice and illustrating their potential positive outcomes for professionals and patients, even though they are not operating as forums for overt knowledge integration for the different professions.